The Use of Terminological Lexicon in Making Phraseological Units - Stojani, Edita; Wrapi, Fatmir (European Journal of Multidisciplinary Studies, 2021)
Terminological lexicon can be found in everyday life, depending on the situation and the speakers. The question that arises is: How can we use technical and scientific terms when the terminological lexicon belongs to a certain language for specific purposes and the specialists of specific fields can use to communicate among themselves by using this lexicon. The use of terms in this form of communication can have various specific lawyers, thus conceptual difficulty. Based on this conclusion we must take into consideration that terminological lexicon is an integral and inseparable part of general lexicon because composites are made from this lexicon, borrowing are taken and structural and semantic calques are made, despite being one-word or multi-word raising them to the level of term and giving them the accuracy and monosemy. Technical and scientific terms depending on the development of the various fields of study, are not used only in communication among specialists but in other fields. This ‘cooperation’ is present in almost all information, data, textbooks and extracurricular books, written press, conversations etc.